2022
DOI: 10.1186/s40168-022-01228-9
|View full text |Cite
|
Sign up to set email alerts
|

Integrated meta-omics reveals new ruminal microbial features associated with feed efficiency in dairy cattle

Abstract: Background As the global population continues to grow, competition for resources between humans and livestock has been intensifying. Increasing milk protein production and improving feed efficiency are becoming increasingly important to meet the demand for high-quality dairy protein. In a previous study, we found that milk protein yield in dairy cows was associated with the rumen microbiome. The objective of this study was to elucidate the potential microbial features that underpins feed effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 77 publications
6
47
0
Order By: Relevance
“…Despite the volume of information on the GIT microbial population, little remains known about how milk yield and milk quality can be impacted by manipulation of the gut microbiota in dairy cattle. Aside from limited assessments of feed efficiency and milk production variables such as lactation stage and milk composition ( Schären et al, 2018 ; Xue et al, 2018 , 2022 ; Buitenhuis et al, 2019 ; Hagey et al, 2019 ), much of the dairy cattle microbiome research has focused on mitigating GIT inflammation or reducing greenhouse gas emissions ( Sanz-Fernandez et al, 2020 ; John et al, 2022 ). Few studies have evaluated the associations between the rumen microbiome and milk yield or quality ( Xue et al, 2018 ; Buitenhuis et al, 2019 ; Hagey et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the volume of information on the GIT microbial population, little remains known about how milk yield and milk quality can be impacted by manipulation of the gut microbiota in dairy cattle. Aside from limited assessments of feed efficiency and milk production variables such as lactation stage and milk composition ( Schären et al, 2018 ; Xue et al, 2018 , 2022 ; Buitenhuis et al, 2019 ; Hagey et al, 2019 ), much of the dairy cattle microbiome research has focused on mitigating GIT inflammation or reducing greenhouse gas emissions ( Sanz-Fernandez et al, 2020 ; John et al, 2022 ). Few studies have evaluated the associations between the rumen microbiome and milk yield or quality ( Xue et al, 2018 ; Buitenhuis et al, 2019 ; Hagey et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Methane not only increases the global greenhouse effect but can also cause animals to lose more than 10% of their energy [ 3 ]. Recent studies have shown that Methanobrevibacter is enriched in the rumens of low-efficiency cows, and the methanogens pathway is also upregulated in low-efficiency cows [ 46 ]. These results demonstrate the negative impact of methanogenic bacteria on ruminants.…”
Section: Discussionmentioning
confidence: 99%
“…The rich microorganisms contained in the rumen are an indispensable link in the digestion of animal nutrients and play a key role in the conversion of plants into milk by dairy cows 12 . Numerous studies have shown that the interactions between rumen microorganisms and the host affect host metabolic processes 13 , 14 . The connection between rumen microbial community composition and change and host production performance is an important breakthrough for heat stress affecting dairy farming technology.…”
Section: Background and Summarymentioning
confidence: 99%